PENGARUH KEPUASAN KERJA TERHADAP INTENSI TURNOVER PADA GURU DI YAYASAN PGRI CIPAYUNG JAKARTA TIMUR AYU SURYANI - AYU SURYANI; Harya Kuncara; Siti Nurjanah (Faculty of Economics, State University of Jakarta., 2014)
The purpose of this research is to gain proper knowledge (legal, valid and true), trustworthy, dependable (reliable) concerning the influence of intense job satisfaction on turnover of teachers in East Jakarta Cipayung PGRI Foundation. This study used a survey, which studied data from samples taken from a populace. Collecting data using a Likert scale questionnaire to variable job satisfaction and turnover intention teacher in East Jakarta Cipayung PGRI Foundation. The sample in this study are all teachers in East Jakarta Cipayung PGRI Foundation (Saturation Sampling). This study uses linear regression analysis. The result is the satisfaction worked intense negative affect turnover. That is, the higher the job satisfaction obtained, the lower turnover intense. In addition, using the f test to determine the significance of the variable to Y produces f of 4.623 with p <0.05, which means there are significant effect all dimensions of job satisfaction on turnover intense. 0.47 shows the determination is meant the proportion of variance explained by the intense turnover entire dimension job satisfaction. The conclusion of this study is that there is significant relationship between the variables of job satisfaction on turnover intention variable. The higher satisfaction received by the teacher, the lower the intention Turnover. So are suggested every teacher should work in a professional manner in order to increase job satisfaction and ultimately reduce intense turnover Keywords: Job Satisfaction, Turnover Intention